Implementing Quilgo to Monitor Online Learning Evaluations: A Qualitative Case Study - Nursyifa Azzahro; Citra Dewi; Naelul Rohmah (Journal of General Education and Humanities, 2025)
The need for a secure and efficient educational evaluation system in the digital era has been growing, especially with the increasing adoption of online exams. However, security and integrity issues remain significant challenges for educational institutions. This study aims to evaluate the effectiveness of Quilgo in addressing these challenges through its personalized registration system and proctoring features. This research involved observations of several educational institutions implementing online exams using Quilgo. It also included interviews with educators and exam participants as the main data sources. The participants were teachers and students with direct experience using Quilgo in various exam settings. The study begins with data collection through direct observation of Quilgo's use in several educational institutions that have adopted online exams and interviews with educators and exam participants. The collected data include user experiences related to registration ease, technical obstacles, and the effectiveness of proctoring features in preventing cheating. The analysis used qualitative and quantitative approaches to assess the application’s efficiency and reliability across different exam scenarios. Moreover, the data analysis process was carried out using behaviorism theory (Skinner, 1963), which highlights the presence of stimuli, responses, and reinforcement—both positive and negative—in the learning evaluation process. The research results show that using personalized link-based registration in Quilgo facilitates registration and enhances security, especially when combined with domain-based email restrictions. Moreover, the proctoring feature that monitors the visual activities of exam participants proved effective in maintaining exam integrity, although challenges related to internet connectivity and device compatibility remain. Despite remaining challenges such as internet connectivity and device compatibility, the results imply that Quilgo has the potential to support more trustworthy and effective online examinations in educational settings.